A Study of Injection Therapy Using bFGF by High‐Speed Imaging and Acoustic Analysis. (2nd September 2014) - Suzuki, Hirotaka; Makiyama, Kiyoshi; Takane, Tomoyuki; Matuzaki, Hiroumi
Abstract : Objectives: Some authors have reported effects of some materials used for injection. Their effects that reduce the size of glottal gap do not last because the materials are usually absorbed. Thus, patients with deficient glottal closure must be repeatedly injected. To reduce the number of treatments, we injected basic fibroblast growth factor (bFGF) into our patients. The purpose of this study was to examine the effect of bFGF injection by high‐speed imaging and acoustic analysis. Methods: Fifteen patients (8 men and 7 women, mean age 65 years) were enrolled in this study. Four or 8 µg of bFGF were injected into each treated vocal cord. The injection was made into the unilateral or bilateral vocal cord according to the size of glottal gap. All patients were followed up every 3 months. Using high‐speed imaging and PS77E, we analyzed the following factors: KEA (kimograph edge analysis), GAW (glottal area wave form), phase shift analysis, PPQ (period pertubation quotient), APQ (amplitude perturbation quotient), MFR (mean flow rates). The effect of the treatment was assessed by high‐speed imaging and acoustic analysis. Results: Data both from the imaging analysis and acoustic analysis showed significant improvement in all subjects after 6 months. No allergic or long‐term adverse effects were noted. Conclusions: The result of this study suggests bFGF may be effective long‐term and safe as a regenerative agent for aged vocal folds.